2019
DOI: 10.1002/bjs.11144
|View full text |Cite
|
Sign up to set email alerts
|

Management of isolated recurrence after surgery for pancreatic adenocarcinoma

Abstract: Background: Recurrence of pancreatic cancer after primary pancreatectomy occurs in the vast majority of patients. The role of surgical treatment for recurrent pancreatic cancer is not well established. Methods: Patients who underwent primary pancreatectomy with curative intent from 2000 to 2014 at a single large-volume centre were evaluated retrospectively. CT or PET was used to select patients with an isolated recurrence. The clinicopathological features and survival outcomes were compared according to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 38 publications
2
41
0
2
Order By: Relevance
“…Recurrence is an important feature of PDAC after surgery, as it contributes to poor prognosis (7). Previous studies have shown that more than 60% of PDAC patients develop tumor recurrence (12). Similar results were also obtained in the present study, in that the patients in this study experienced a recurrence rate of 57.3%.…”
Section: Discussionsupporting
confidence: 90%
“…Recurrence is an important feature of PDAC after surgery, as it contributes to poor prognosis (7). Previous studies have shown that more than 60% of PDAC patients develop tumor recurrence (12). Similar results were also obtained in the present study, in that the patients in this study experienced a recurrence rate of 57.3%.…”
Section: Discussionsupporting
confidence: 90%
“…Pancreatic cancer has an extremely poor prognosis even after surgical resection. Recurrence was observed in more than 60% of all PDAC patients after surgery (4, 16) and remained the main reason of poor prognosis in these patients. In this study, recurrence was observed in 57.3% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although long-term follow-up is required to address the potential role of repeated pancreatectomy for recurrent pancreatic cancer, recent studies and the present pooled analysis strongly suggest the oncologic benefits of this approach [36,37]. In the present study, the median OS was estimated to be 60 months from the time of repeated pancreatectomy and 107 months from the time of initial radical pancreatectomy.…”
Section: Discussionmentioning
confidence: 59%